2000
DOI: 10.1111/j.0901-9928.2000.860602.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Silibinin on Cytochrome P‐450 Enzymes in Human Liver Microsomes

Abstract: Silibinin, the main constituent of silymarin, a flavonoid drug from silybum marianum used in liver disease, was tested for inhibition of human cytochrome P-450 enzymes. Metabolic activities were determined in liver microsomes from two donors using selective substrates. With each substrate, incubations were carried out with and without silibinin (concentrations 3.7-300 mM) at 37ae in 0.1 M KH 2 PO 4 buffer containing up to 3% DMSO. Metabolite concentrations were determined by HPLC or direct spectroscopy. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
101
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 31 publications
2
101
3
Order By: Relevance
“…MTX inhibits the synthesis of DNA, RNA, thymidylate and proteins. As a result of this activity, MTX is commonly used in cancer treatment, in addition to the treatment of non-neoplastic diseases, including rheumatoid arthritis and psoriasis (1). Previous studies have demonstrated that liver, kidney, brain and lung toxicities are potential side effects of MTX use (2).…”
Section: Introductionmentioning
confidence: 99%
“…MTX inhibits the synthesis of DNA, RNA, thymidylate and proteins. As a result of this activity, MTX is commonly used in cancer treatment, in addition to the treatment of non-neoplastic diseases, including rheumatoid arthritis and psoriasis (1). Previous studies have demonstrated that liver, kidney, brain and lung toxicities are potential side effects of MTX use (2).…”
Section: Introductionmentioning
confidence: 99%
“…The active constituents of S. marianum may strengthen or stimulate the immune response by interacting with various parameters of the immune system. The reported positive effect of herbal medicine has been expressed by a number of mechanisms, e.g., inhibition of tumor necrosis factor TNF-α, interferon IFN-γ, interleukin IL-2, IL-4, and nuclear factor-kappa B (NF-ĸB) activation in rat (Wilasrusmee et al 2002, Ardestani andYazdanparast 2007), inhibition of fibrosis in rat (Jia et al 2001), inhibition of inflammation (Kaur andAgarwal 2007, Ramasamy andAgarwal 2008), immunomodulation in mice (Schümann et al 2003), inhibition of mitochondrial injury in rat (Rolo et al 2003), inhibition of P450 activity in human liver microsomes (Beckmann-Knopp et al 2000), antioxidant properties and inhibition of lipid peroxidation in rat and fish (Han et al 2007, Toklu et al 2007, Banaee et al 2011, enhancement of RNA, DNA (Sonnenbichler et al 1984), protein synthesis in liver tissue of rainbow trout (Banaee et al 2011), regulation of cell permeability (Kiruthiga et al 2007, Basiglio et al 2009), and adjustment of enzyme levels activity in plasma (Banaee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the administration of silymarin is considered safe with minimal adverse events, the competitive interaction of silybin with cytochromes P450 (P450s 1 ) and the potential for drug interactions were recently reported (Beckmann-Knopp et al, 2000). The importance of phase I biotransformation, mainly facilitated by cytochromes P450, in the oxidative metabolism and eventual detoxification of drugs and xenobiotics is well recognized (Guengerich, 1991).…”
mentioning
confidence: 99%
“…Importantly, glucuronidation facilitated by UDP-glucuronosyltransferases (UGTs) is increasingly recognized as a major phase II detoxification pathway in humans (Fisher et al, 2001), and silybin may exert effects on both phase I and phase II metabolic reactions. For instance, silybin has been shown to noncompetitively inhibit denitronifedipine oxidation, mediated by P450 3A4 (K i ϭ 11 M), in human liver microsomes (Beckmann-Knopp et al, 2000). Competitive inhibition was reported for S(Ϫ)-warfarin 7-hydroxylation (P450 2C9; K i ϭ 19 M).…”
mentioning
confidence: 99%
See 1 more Smart Citation